2023
DOI: 10.1186/s12910-023-00928-7
|View full text |Cite
|
Sign up to set email alerts
|

Institutional review boards in Saudi Arabia: the first survey-based report on their functions and operations

Abstract: Background Institutional review boards (IRBs) are formally designated to review, approve, and monitor biomedical research. They are responsible for ensuring that researchers comply with the ethical guidelines concerning human research participants. Given that IRBs might face different obstacles that cause delays in their processes or conflicts with investigators, this study aims to report the functions, roles, resources, and review process of IRBs in Saudi Arabia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Participants did not express the need for continuous training for their members who were assumed to be knowledgeable because of their seniority which overlooks the pivot of keeping REC members in line with emerging research ethics topics, such as gene editing or arti cial intelligence. This inconsistency of requiring ethics training has been documented by research in the region by (6) in Jordan and (11) in Sub-Saharan Africa showing that it is not seen to be necessary; while other research studies in Saudi Arabia describe proper training mechanisms and guidance for RECS (7). REC members in Saudi Arabia are required by law (Law of Ethics of Research on Living Created by the National Committee of Bio-Ethics NCBE) to complete training on ethics and regulations in order to be registered (7), which could explain the attention to this training initiative there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants did not express the need for continuous training for their members who were assumed to be knowledgeable because of their seniority which overlooks the pivot of keeping REC members in line with emerging research ethics topics, such as gene editing or arti cial intelligence. This inconsistency of requiring ethics training has been documented by research in the region by (6) in Jordan and (11) in Sub-Saharan Africa showing that it is not seen to be necessary; while other research studies in Saudi Arabia describe proper training mechanisms and guidance for RECS (7). REC members in Saudi Arabia are required by law (Law of Ethics of Research on Living Created by the National Committee of Bio-Ethics NCBE) to complete training on ethics and regulations in order to be registered (7), which could explain the attention to this training initiative there.…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency of requiring ethics training has been documented by research in the region by (6) in Jordan and (11) in Sub-Saharan Africa showing that it is not seen to be necessary; while other research studies in Saudi Arabia describe proper training mechanisms and guidance for RECS (7). REC members in Saudi Arabia are required by law (Law of Ethics of Research on Living Created by the National Committee of Bio-Ethics NCBE) to complete training on ethics and regulations in order to be registered (7), which could explain the attention to this training initiative there. If such policies and laws that require continuing education for RECs and researchers, were to be developed and enforced then all parties involved in research and research oversight would bene t.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the IRBs review 40 protocols of clinical trials annually, and the duration of each meeting is around 45-120 min. The average number of days taken for the full committee review is 20.5 days [40]. This might be the reason that researchers are reluctant to have the full board review every project.…”
Section: Knowledge Of the Existence And Significance Of Irb Statementsmentioning
confidence: 99%
“…Also, researchers had the least positive attitude toward the statement that "the IRB should have an unaffiliated member (non-medical person)" (47.92%). In a survey by Al Fattan et al (2022) [40], it was reported that only 30.7% of the members of the IRB in Saudi Arabia were non-scientific members. In a survey conducted among non-affiliated IRB members, 88% agreed that having nonscientist IRB members is one of the reasons for making research more accountable to the public [41].…”
Section: Knowledge Of the Existence And Significance Of Irb Statementsmentioning
confidence: 99%